Aspartate aminotransferase-to-platelet ratio predicts response to transarterial chemoembolisation and prognosis in hepatocellular carcinoma patients. Issue 3 (March 2018) - Tang, T.; Qiu, J.-L.; Li, G.-W.; Huang, M.-P.; Li, Y.; Li, Y.-J.; Gu, S.-Z.
Abstract : Aim: To evaluate the value of the aspartate aminotransferase-to-platelet ratio index (APRI) for hepatocellular carcinoma (HCC) patients who underwent transarterial chemoembolisation (TACE). Materials and methods: A total of 315 patients were enrolled, who were randomly divided into the training cohort ( n= 158) and the validation cohort ( n= 157). The optimal cut-off value of the APRI was determined using the X-tile software in the training cohort, and was validated in the validation cohort. Several serum-based markers, neutrophil-to-lymphocyte (N/L) and aspartate aminotransferase-to-alanine aminotransferase (AST/ALT) ratios were included to compare with the APRI. To predict individual survival rate, independent predictors were included to build a nomogram. Results: Using the X-tile, a cut-off value of the APRI as 0.40 was yielded to distinguish patients with distinct outcomes in the training cohort, but failed for the N/L and ALT/AST ratios. In the training cohort, 66 patients with high APRI had poorer survival ( p< 0.001) than did 92 patients with low APRI. Using the same cut-off value of APRI, 61 patients with high APRI had poorer survival ( p< 0.001) than did 96 patients with low APRI in the validation cohort. Furthermore, a nomogram, including the APRI, TACE cycles, tumour size, and tumour number, was built based on the training cohort, and validated well in the validation cohort (concordance index [C-index] 0.713). Conclusion: The APRI is a promising marker to predict treatment response and outcome for HCC patients after TACE treatment. Highlights: The APRI is superior to the N/L, AST/ALT ratios in predicting survival for HCC patient after TACE treatment. The APRI is a serum-based marker to predict TACE response before treatment administrated. The nomogram, including the APRI, is a valid tool to predict individual patient's survival in clinical routine.